Evaluation of motor skills in children participating in social/sports projects Avaliação das habilidades motoras de crianças participantes de projetos sociais/esportivos - Santos A.M.* (2013)
Besides the biological evolutionary process, studies have shown that environmental and social factors can influence the motor development. The aim of this study was to evaluate the motor skills of students participating in social educational projects, sports projects and those not engaged in structured extracurricular activities in Florianópolis - SC - Brazil.Were evaluated 136 children 8 - 9 years old, both sexes, from 40 public schools. For data collection was used the Motor Development Scale and a structured interview regarding the activities undertaken by the child during the period that they are not in school. Descriptive statistics, ANOVA and the Post-hoc test of Tukey were used to data analysis, with significance level p < .05. The results showed higher patterns of motor development in children that participating in social projects with sport character and expressive low coordination patterns in children who do not participate in structured activities or projects outside of school. © FTCD/FIP-MOC.